Current Trends in Orthopaedic Surgery Residency Applications and Match Rates. (18th March 2020) - Trikha, Rishi; Keswani, Aakash; Ishmael, Chad R.; Greig, Danielle; Kelley, Benjamin V.; Bernthal, Nicholas M.
Abstract : Background: The current U.S. orthopaedic residency application process is becoming increasingly impersonal in the wake of an increasing number of applications. Through an analysis of orthopaedic surgery residency application statistics, we have highlighted the effect that the number of orthopaedic applications has on match rate, and we have suggested methods for a more personalized application process. Methods: Data from the Association of American Medical Colleges (AAMC) and the National Resident Matching Program (NRMP) for United States orthopaedic residency applicants from 2008 to 2018 were collected. These data included the average number of applications submitted per applicant, the average number of applications received per program, the total number of residency positions offered in the U.S., the total number of U.S. applicants, and the total number of U.S. applicants who matched to a U.S. orthopaedic surgery residency program. U.S. applicant match rates and the average number of applications received per residency position offered were calculated. Linear regression models were used to determine the rate at which these variables changed over time. Results: The average number of applications submitted by an applicant increased from 46.5 in 2008 to 74.9 in 2018. The average number of applications received per residency position offered increased from 54.1 in 2008 to 85.7 in 2018. The number of U.S. applicants was 740 in 2008 and 849 in 2018. The number of U.S. orthopaedic residency programs only slightly increased from 160 in 2008 to 171 in 2018. The match rate for U.S. medical school applicants has remained stable from 2008 to 2018 at a mean of 76.9% and a standard deviation of 2.3%. Conclusions: The match rate has remained stable from 2008 to 2018 despite an increase in the number of applications per position. This discrepancy suggests that increasing the number of submitted applications may not correlate with applicant success. We address this discrepancy and suggest methods that can potentially allow for a more targeted orthopaedic application experience.